Export-Learning and FDI with Heterogeneous Firms - JAKOBSSON, Amanda (Institutional Knowledge at Singapore Management University, 2015)
I present a dynamic general equilibrium model with heterogeneous firms that can innovate, learn how to export and then go on to become multinational firms. Entering the foreign market is a dynamic process where firms first learn how to export and then can learn how to adapt production to a low-wage location (multinational production). I solve the model numerically and, starting from a 1990 benchmark of US and Mexico, study how policy changes such as stronger patent protection and trade liberalization affect innovation, technology transfer and consumer welfare. In particular, I disentangle how labor resources are reallocated within regions in response to policy changes: across sectors (production, innovation, export-learning and adaption to multi-national production), across high-productivity and low-productivity firms, and within firms as they produce more (less) for the home market visavi the export market. I obtain higher rates of export-learning and FDI for high-productivity firms than for low-productivity firms. As a result, exporters are on average more productive than non-exporters, and multinational firms are on average more productive than exporters. In equilibrium, there are still some low-productivity exporters, some low-productivity multinational firms and some high-productivity non-exporters. Low-productivity firms export and engage in FDI but they are just not as successful in these activities as high-productivity firms.